Prevalence and determinants of excessive daytime sleepiness among resident doctors at a tertiary care institution in India - H. S., Siddalingaiah; Mastin, David F.; Moore, Bruce D.; Bryson, W. Jeff; D., Chandrakala; Singh, Amarjeet (International Journal Of Community Medicine And Public Health, 2018)
Background: Modern socio-occupational settings, especially medical settings, often involve shift work, long work hours, and concomitant maladaptive sleep habits. These factors may result in daytime sleepiness, an increase in the prevalence of sleep disorders, and/or an exacerbation of existing sleep disorders in the contemporary workforce. Aim was to measure the prevalence and determinants of excessive daytime sleepiness (EDS) among medical residents at a Tertiary Care Institution in India. Methods: A cross-sectional study was designed and a list of all enrolled medical residents was obtained (N=430). The eligible subjects (N=428) were interviewed and administered the study instruments. The information on socio-demographics and sleep-related factors were collected using the sleep assessment proforma. The Epworth sleepiness scale (ESS) was used to measure excessive daytime sleepiness (EDS) and the sleep hygiene index (SHI) was used to measure sleep hygiene. Data were analyzed with appropriate statistical methods. Results: A total of 350 residents responded (82%). The prevalence of EDS and Maladaptive sleep hygiene were 47.4% and 85.5% respectively. A positive association was found between EDS and weekly work hours, SHI score, sleep duration, sleep quality, midnight awakenings, clinical stream, and rotating shift work. Coffee intake and smoking within 4 hours of bedtime, restless legs and allergies had weak association with EDS. Conclusions: EDS and unhygienic sleep were highly prevalent among resident doctors. The factors associated with EDS were mainly related to work, sleep quantity, sleep quality and sleep hygiene which are amenable to suitable modifications by behavioural change communications, awareness programs and by administrative actions.